To solve the expression \((1/2 + 1/5) - (3/8 + 1/4)\), we will first simplify the two parts separately before combining the results.
Step 1: Simplify \(1/2 + 1/5\)
To add the fractions, we need a common denominator. The least common multiple of 2 and 5 is 10.
\[ 1/2 = 5/10 \quad \text{and} \quad 1/5 = 2/10 \]
Adding them together:
\[ 1/2 + 1/5 = 5/10 + 2/10 = 7/10 \]
Step 2: Simplify \(3/8 + 1/4\)
The least common multiple of 8 and 4 is 8.
\[ 1/4 = 2/8 \]
Adding these:
\[ 3/8 + 1/4 = 3/8 + 2/8 = 5/8 \]
Step 3: Subtract the two results
Now, we need to compute:
\[ (7/10) - (5/8) \]
To subtract these fractions, we need a common denominator. The least common multiple of 10 and 8 is 40.
Convert \(7/10\) and \(5/8\) to have a denominator of 40:
\[ 7/10 = 28/40 \quad (\text{since } 7 \times 4 = 28) \] \[ 5/8 = 25/40 \quad (\text{since } 5 \times 5 = 25) \]
Now subtract:
\[ 28/40 - 25/40 = (28 - 25)/40 = 3/40 \]
Therefore, the final answer is:
\[ \boxed{3/40} \]